Identification and isolation of a variant surface glycoprotein from Trypanosoma vivax - Gardiner, Peter R.; Pearson, T.W.; Clarke, M.W.; Mutharia, L.M. (American Association for the Advancement of Science, 1987)
The protozoan Trypanosoma vivax is one of the most important agents of African trypanosomiasis, a disease that hinders the productive use of livestock in one-third of the African continent. Trypanosoma vivax is also present in the Caribbean and in South America, posing a threat to the livestock industries of the tropical and subtropical world. Much less is known of the biology of this trypanosome than of the better studied T. brucei and T. congolense . One of the variant surface glycoproteins (VSGs) of a West African stock of T. vivax was identified, purified, and partially characterized by the use of a combination of highly resolving techniques to maximize information from the relatively small amount of parasite material available. The molecular weight of the isolated protein (46,000) is smaller than that of VSGs from other species. As with T. brucei VSGs the protein from T. vivax is complexed with sugars and incorporates 3 H when living trypanosomes are incubated with [ 3 H]myristic acid, but the T. vivax molecule is more hydrophobic than the T. brucei molecule. The small size of the T. vivax VSG may have a bearing on the functional and evolutionary relationships of variant antigens in trypanosomes.